Does wisdom matter? A case study of strategic school leaders - Mohd Ali, Hairuddin (Institut Aminuddin Baki, 2009)
Ministry of Education Malaysia (MoEM) formulated an Educational Master Plan (2006-2010) to ensure the achievement of National Mission. It is a continuation of the previous plan that emphasized on accessibility, equity and as well as to enhance the educational management and leadership effectiveness and efficiency aspect. The purpose of this paper is to examine the strategic leadership characteristics for Quality Malaysian National Primary School Leader (QMNPSL) and how the findings of the study implicate the present practices of educational management and leadership that are pertinent to the quality of education. Approximately 600 senior management team comprised senior teachers from 150 schools were randomly selected to complete the 10-pages survey questionnaires (52 seven-point Likert scale items). The collection centre received approximately 420 completed survey questionnaires from the sampled schools. The employment of data screening process finally omitted 14 out of 420 cases prior to further data analysis. SPSS 15.0 (specifically principal component analysis) was used to determine the underlying factors of the strategic leadership characteristics of the school leaders. The study also employed a full fledge Structural Equation Modeling (SEM) software AMOS 16.0 and SPSS 15.0 to confirm the dimensionality and the psychometric of the scales respectively. Although Davies and Davies (2004) suggested that strategic school leaders must posses all nine (9) strategic characteristics, however the study confirmed that QMNPSL only posses six (6) out of nine stipulated characteristics. One out of 2 missing characteristics was ‘wisdom’, which is extremely important for an efficient and effective leadership in his/her capacity to realize the MoEM Mater Plan particularly at grassroots level. Hence, without proper effective actions taken, the future of Malaysian primary education will be at stake. The findings from the study provide useful information to senior management team members of the respective schools, District and State Education Department. IAB as an educational and leadership training wing for MoEM perhaps need to restructure its training curriculum and the delivery of training as well, AT least these three pertinent aspects, to certain extent will contribute to the achievement of the goals (mainly accessibility, equity, quality and as well as to enhance the educational management effectiveness and efficiency) stipulated in the MoEM Education Master Plan (2006-2010).